A Analysis of Digital Transformation in Public Services (Case Study: Banyumas Regency Public Service Mall) - Falih Suaedi; Muhammad Zulfikar (Yayasan Ilomata, 2023)
The application of e-government in the form of information technology in government institutions is an effort to revitalize the implementation of public administration tasks and functions in policy management or service delivery. One of how public management is implemented through the concept of e-government is implemented in the Public Service Mall, which in the process cannot be separated from digital transformation. Digital transformation in public services refers to processes and strategies that use digital technology to realize services that are clean, transparent, and can respond effectively to changing demands. This research was conducted using a qualitative descriptive approach. This research analysis uses the theory of digital transformation of public services which is used as a measuring instrument to determine the implementation of digital transformation in public services at the Banyumas Regency Public Service Mall referring to six dimensions. The data collection technique was carried out using a literature study so that primary data was obtained from various literatures online. The results of the study reveal that most of the dimensions of digital transformation in Banyumas Public Service Mall services are considered very good. Four dimensions, namely the dimensions of Accessibility, Awareness, Accountability, Origin of data, privacy, and fairness, are considered very good. The other dimensions, namely Accountability and Explanation, can be considered good.